Perspectives of institutional investors on the issue of corporate governance. - Sum, Pey Shan. (2008)
Institutional investors play an increasingly important role in corporate governance nowadays. There have been several cases, such as in the United States and the United Kingdom, where institutional investors were able to use their influence to force changes in under-performing companies. They play a more active role today and take into consideration corporate governance issues when making investment decisions. The objective of this study is to find out the perspectives and viewpoints of the institutional investors in Singapore in relation to corporate governance issues. The project explores six important aspects of corporate governance which include the institutional investors, Board of Directors, chairman of the Board and Chief Executive Officer, audit committee, internal auditors and external auditors and the regulators.